Operational and Strategic Learning in Global Software Development - Implications from two Offshoring Case Studies in Small Enterprises - Boden, Alexander; Nett, Bernhard; Wulf, Volker; Wulf, Volker; Boden, Alexander; Nett, Bernhard (IEEE software, 2019)
Small to medium-sized software enterprises (SME) increasingly participate in offshoring activities. Detecting market niches and deploying highly flexible software development approaches are seen as key competitive abilities of SME. Therefore, it is of major importance to learn how offshoring affects these capabilities which are closely related to organizational learning. We present case studies from two German companies that engage in offshoring of software development. By comparing the cases with each other, we highlight the different structures the companies chose for their development work and how these structures were enacted in practice. Furthermore, we show how related practices affect strategic and operational aspects of Argyris et al.’s (1985) conception of single- and double-loop learning. Our case studies show that organizational learning is a problem for SME engaged in offshoring and that an inability for double-loop learning can even lead to failures in case of organizational restructuring.